The Effect of Integration on Business Strategies - Gbenga Fapohunda; Asunmo Olakunle Olayide (Communications of International Proceedings, 2023)
The study assessed how integration affect business strategies by evaluating the impact of forward and backward vertical integration on business performance. The data used in the testing of hypotheses formulated in the study was analyzed using the regression technique.  The result shows that forward and backward integrations have a positive and significant effect on performance. The study concluded that forward and backward integrations are the major determinants of business performance. The study recommends that management implement integration in their strategic plan to enhance their business operations in order to boost their operations and increase performance.
Keywords: Integration; Forward Integration; Backward Integration; Performance.